2009
DOI: 10.2136/vzj2008.0134
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Monitoring of Water Percolation and Solute Transport Using a Vadose Zone Monitoring System

Abstract: Water percolation and tracer migration through the vadose zone underneath an ephemeral channel were studied using a vadose zone monitoring system (VMS) and application of a multitracer test. The VMS included flexible time‐domain reflectometry (FTDR) probes for continuous tracking of water content profiles, and vadose zone sampling ports (VSPs) for frequent sampling of the deep vadose pore water at multiple depths. The VMS was installed directly under an infiltration pond with several infiltration rings contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(90 citation statements)
references
References 37 publications
2
82
0
Order By: Relevance
“…The VMS is designed to collect in situ real-time continuous measurements of the water contents and the temperatures in the vadose zone, using flexible time domain reflectometry probes (FTDRs) and thermocouples, respectively, and to allow frequent sampling of the sediment pore water, using vadose zone sampling ports (VSPs) (Dahan et al, , 2009Rimon et al, 2007Rimon et al, , 2011. The VSPs are essentially suction lysimeters that have been modified for operation with the VMS in deep sections of the vadose zone.…”
Section: Monitoring Sampling and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The VMS is designed to collect in situ real-time continuous measurements of the water contents and the temperatures in the vadose zone, using flexible time domain reflectometry probes (FTDRs) and thermocouples, respectively, and to allow frequent sampling of the sediment pore water, using vadose zone sampling ports (VSPs) (Dahan et al, , 2009Rimon et al, 2007Rimon et al, , 2011. The VSPs are essentially suction lysimeters that have been modified for operation with the VMS in deep sections of the vadose zone.…”
Section: Monitoring Sampling and Analysismentioning
confidence: 99%
“…The VSPs are essentially suction lysimeters that have been modified for operation with the VMS in deep sections of the vadose zone. Pore-water sampling from unsaturated sediments is achieved by creating hydraulic continuity between the sediment and the sampling cell using a flexible porous interface (Dahan et al, 2009;Patents # US 6,956,381; US 12/222,069; EP 07706061.4; IL 193126). Detailed descriptions of the VMSs' setup and the monitoring probes used in this study can be found in previous publications by Baram et al (2012a, b).…”
Section: Monitoring Sampling and Analysismentioning
confidence: 99%
“…1). Full technical descriptions of the VMS structure, performance and installation procedures can be found in other publications (Rimon et al, 2007(Rimon et al, , 2011Dahan et al, 2008Dahan et al, , 2009). For brevity, only a general description is given here.…”
Section: Monitoringmentioning
confidence: 99%
“…The recent development of a vadose-zone monitoring system (VMS) enables continuous monitoring of the hydrological and chemical properties of percolating water in the deep vadose zone under agriculture settings (Turkeltaub et al, 2014(Turkeltaub et al, , 2015b and other hydrological settings (e.g., Dahan et al, 2009;Baram et al, 2013). Data collected by the system comprise direct measurements of the water-percolation fluxes and the chemical evolution of the percolating water across the entire unsaturated zone.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous approaches have been developed to investigate the hydraulic properties of riverbed, including grain-size distribution analysis (Alyamani and Sen, 1993), in-stream methods (Cardenas and Zlotnik, 2003;Chen, 2000;Landon et al, 2001;Rosenberry, 2008), environmental tracer experiments (Anderson, 2005;Constantz, 2008;Roshan et al, 2012;Vogt et al, 2012), a vadose zone monitoring system (Dahan et al, 2007(Dahan et al, , 2009), water balance techniques (Fleckenstein et al, 2010;Kalbus et al, 2006;Shanafield and Cook, 2014), and integrated surface-groundwater numerical modelling (Boano et al, 2013;Brunner et al, 2010;Doppler et al, 2007;Lautz and Siegel, 2006). The hydraulic properties of the riverbed, which are estimated using the aforementioned methods, are mostly assumed to be constant over time in studies on riverbank filtration processes and the related surface-groundwater interactions (Baveye et al, 1998).…”
Section: Introductionmentioning
confidence: 99%